Studying the performance of cutting carbon fibre-reinforced plastic using an abrasive water jet technique - Hussien, Ahmed A. (Strojniški vestnik, 2021)
In recent years, composite materials such as carbon-fibre-reinforced plastic (CFRP) have been widely used in medical devices, industries, marine and aerospace applications due to their high resistance-to-weight ratio toughness, corrosion resistance, and other novel properties. The machining of these composite materials using conventional machines results in poor precision and surface finishing due to excess heat generation at the tool-material contact zone. The drawbacks of the conventional machining process can be overcome with the adoption of a novel cutting technique using pressurized water, which can dissipate the heat generated by the impact of abrasive particles against the material in order to eliminate the poor precision and surface finishing caused by overheating. In this experimental study, the performance of surface quality (roughness and kerf angle) of CFRP machining using an abrasive water jet technique has been studied for a wide range of cutting parameters, such as water pressure and cutting speed.
Keywords: abrasive water jet; abrazivni vodni curek; CFRP; composite materials; hrapavost; kakovost površin; kerf angle; kompozitni materiali; kot reže; rezanje; roughness; surface quality